Modeling and Valuation of Energy Structures Analytics, Econometrics, and Numerics - Mahoney, Daniel; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book is a comprehensive guide to quantitative and statistical approaches that have been successfully employed in support of trading operations.
Keywords: Energy policy; Energy and state; Business mathematics; Finance; Mathematics; Econometrics; Economics; Econometrics; Finance, general; Business Mathematics; Energy Policy, Economics and Management; Mathematics, general; Electronic books